PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN KARAKTER JUJUR PESERTA DIDIK MELALUI PROBLEM-BASED LEARNING BERNUANSA ISLAMI - Ekaningtyas, Maya; Sulastri, Yayu Laila; Nurjanah, Nurjanah (Universitas Islam Nusantara, 2023)
This research is motivated by the low ability to understand mathematical concepts and the honest character of students. One alternative learning model that can be applied is Problem-Based Learning with Islamic nuances. The purpose of this study was to determine differences in the ability to understand mathematical concepts and the honest character of students who studied with the Islamic-nuanced Problem-Based Learning model and students who studied with the contextual nuanced Problem-Based Learning model, as well as to find out the criteria for the value of students' honesty after participating in Problem-Based Learning with Islamic nuances. The method used is a quasi-experimental method with the Nonequivalent Control Group Design research design. This research was conducted at MTs Al-Huda Rancaekek. The population in this study were all students in class VII MTs Al-Huda Rancaekek, the sample in this study were students in class VII-A as the experimental class and students in class VII-B as the control class. The experimental class learns using the Problem-Based Learning model with Islamic nuances, the control class learns using Problem-Based Learning with contextual nuances. The instruments used were tests of ability to understand mathematical concepts, honest character observations, and self-assessment questionnaires. Based on the results of the Mann-Whitney test analysis, observation analysis, and self-assessment questionnaire analysis, it was concluded that there were differences in the understanding of mathematical concepts of students who studied with Problem-Based Learning with Islamic nuances and students who studied with Problem-Based Learning with contextual nuances. The criteria for the value of honest character attitudes of students after participating in Problem-Based Learning with Islamic nuances are in the MB criteria (starting to develop). Keywords: Problem-Based Learning with Islamic Nuances, Ability to Understand Mathematical Concepts, and Honest Character.